Siachen : Conflict Without End - Raghavan, V. R. (Lt. Gen.) (New Delhi, India Viking, 2002)
Comprehensive assessment of strategic importance of Siachen glacier leads to conflict between Indian and Pakistan.
Include Appendix And Index
Keywords: Pakistan -- India -- Military relations